KASIH SEBAGAI DASAR MEMBANGUN PERSAUDARAAN: Kita Terpanggil untuk Menghadirkan Kasih Sebagai Dasar untuk Membangun Brotherhood di Tengah-tengah Gereja dan Masyarakat - Parsaulian Simorangkir (Universitas Methodist Indonesia, 2024)
In the midst of this modern era, it feels like people are starting to forget the meaning of Christian brotherhood. The practice of exercising compassion is increasingly fading, especially since people are increasingly busy in their own world. Now, modern humans are more likely to be